A Tale of 3 Tracers: Contrasting Uptake Patterns of 18F-Fluciclovine, 68Ga-PSMA, and 18F-FDG in the Uterus and Adnexa. (6th January 2023) - Lawal, Ismaheel O.; Adediran, Omotayo Atinuke; Muzahir, Saima; Friend, Sarah; Bhave, Manali Ajay; Meisel, Jane; Torres, Mylin A.; Styblo, Toncred Marya; Graham, Cathy; Holbrook, Anna; Kalinsky, Kevin; Fielder, Bridget; et al.
Abstract: A 41-year-old woman with invasive lobular carcinoma of the breast underwent sequential 68 Ga-PSMA-11 PET/CT and 18 F-fluciclovine PET/CT as part of an ongoing clinical trial (NCT04750473). 68 Ga-PSMA PET/CT showed increased radiotracer uptake in the uterine endometrium and left adnexa. 18 F-fluciclovine PET/CT showed increased radiotracer uptake in a leiomyomatous uterus. A clinical 18 F-FDG PET/CT demonstrated radiotracer uptake in the endometrium and a circumferential area of uptake in the left adnexa, a pattern more similar to the 68 Ga-PSMA uptake pattern. This case highlights the discordance in the uptake pattern of 2 radiotracers approved for prostate cancer imaging but increasingly used in non-prostate malignancies imaging.